STRONGHOLD first-year results of biomechanically calculated abdominal wall repair: a propensity score matching - Lesch, Carolin; Nessel, R.; Adolf, D.; Hukauf, M.; Köckerling, F.; Kallinowski, Friedrich; Willms, A.; Schwab, R.; Zarras, K. (Hernia, 2023)
Purpose: Every year around 70,000 people in Germany suffer from an abdominal incisional hernia that requires surgical treatment. Five years after reconstruction about 25% reoccur. Incisional hernias are usually closed with mesh using various reconstruction techniques, summarized here as standard reconstruction (SR). To improve hernia repair, we established a concept for biomechanically calculated reconstructions (BCR). In the BCR, two formulas enable customized patient care through standardized biomechanical measures. This study aims to compare the clinical outcomes of SR and BCR of incisional hernias after 1 year of follow-up based on the Herniamed registry. Methods: SR includes open retromuscular mesh augmented incisional hernia repair according to clinical guidelines. BCR determines the required strength (Critical Resistance to Impacts related to Pressure = CRIP) preoperatively depending on the hernia size. It supports the surgeon in reliably determining the Gained Resistance, based on the mesh-defect-area-ratio, further mesh and suture factors, and the tissue stability. To compare SR and BCR repair outcomes in incisional hernias at 1 year, propensity score matching was performed on 15 variables. Included were 301 patients with BCR surgery and 23,220 with standard repair. Results: BCR surgeries show a significant reduction in recurrences (1.7% vs. 5.2%, p = 0.0041), pain requiring treatment (4.1% vs. 12.0%, p = 0.001), and pain at rest (6.9% vs. 12.7%, p = 0.033) when comparing matched pairs. Complication rates, complication-related reoperations, and stress-related pain showed no systematic difference. Conclusion: Biomechanically calculated repairs improve patient care. BCR shows a significant reduction in recurrence rates, pain at rest, and pain requiring treatment at 1-year follow-up compared to SR.